Mengelola Untuk Bertumbuh: Analisis Data Panel Tentang Peran Tata Kelola Perusahaan Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Anisaul Hasanah; Parasdya Pandhu Andanawarih (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study investigates the influence of board independence, gender diversity, audit committee, institutional ownership on financial performance. Current literature provides various findings explaining the effect of corporate governance on financial performance. This study introduces a novel approach by integrating ROE and ROA as metrics of financial performance, a topic not extensively covered in the literature, particularly in the context of Indonesia. This study employs a panel regression model with fixed effects using data from 396 firm-year observations. The findings indicate a negative impact of gender diversity, audit committee, institutional ownership on financial performance. However, board independence indicates a positive impact on financial performance. Our study differs from previous research because we employ two measurement proxies ROA and ROE as indicators of financial performance, whereas prior studies typically used only one of these measures.